Souvislost mezi řízením vztahů k zákazníkům (CRM) a tržní orientací (MO) a vliv velikosti podniku a typu trhu na CRM a MO - Frejková, Daniela; Chalupský, Vladimír (Vysoké učení technické v Brně, Fakulta podnikatelská, 2013)
Purpose of the article: This paper is concerned with Market Orientation (MO) and Customer Relationship Management (CRM). These two topics have been frequently explored in the field of corporate management and marketing. Nevertheless, these two concepts are still analyzed separately in the literature. This article explains why these concepts are interdependent and sets the degree of dependence of these concepts. It also finds out whether the level of MO and CRM is dependent on company size or the type of market. Methodology/methods: This article has been prepared based on the analysis of secondary and primary sources. The primary research was conducted on a sample of 29 completed questionnaires provided by firms from the aerospace field in the Czech Republic. The level of CRM and MO was determined for each company and a statistical verification was conducted. Scientific aim: One aim of this article is to reveal the interconnections between MO and CRM. Other aim is to determine whether CRM and MO are affected by the size of the company and whether they depend on the type of market (business-to-business, i.e. B2B or business-to-customer, i.e. B2C). Findings: Findings of this article are new information in this area. The data strongly support the proposition that MO is interconnected with CRM, while no dependence on the size of the company or the type of market has been confirmed. Conclusions: This research supports the opinion that MO and CRM are appropriate for each of the researched type of the company (under certain conditions). The findings must be considered within the limitations of this study. Conclusions for the whole business may be drawn after the comparison of experiences across business sectors from different countries.
Connection between Customer Relationship Management (CMR) and Market Orientation (MO) and the Influence of Size of a Company and Type of Market on CRM and MO
Keywords: Customer Relationship Management; Market Orientation; business-to-business; business-tocustomer; size of company